Analysis of structures and application of different types of engines in cars - Kuzhelnyi, Yaroslav; Venzheha, Volodymyr; Pasov, Hennadiі; Klymenko, Valeriy; Кужельний, Ярослав Володимирович; Венжега, Володимир Іванович; Пасов, Геннадій Володимирович; Клименко, Валерій Іванович (Харківський національний автомобільно-дорожній університет, 2023)
Problem. The publication analyzes the structures and application of various types of engines in a car, which allows to determine the structural aspects, features of placement and operation of engines, their future application prospects. Purpose. The purpose of the work is to analyze the design and operation of engines used in modern cars, to determine their advantages and disadvantages, and the prospects for the development and application of various types of engines. Methodology. The approaches adopted in the work to achieve the set goal consist in the analysis of designs of various types of engines of modern cars, their layout and features of their use. Results. The paper includes a comparative analysis of various types of engines used in modern cars. The peculiarity of the design and structure of internal combustion engines, electric cars and hybrid cars is considered. The scheme of the general configuration of electric vehicles, possible configurations of electric vehicles, layout schemes of hybrid cars are given. The advantages and disadvantages of each type of engine, the main prospects for their development and application are shown. Originality. The conducted analysis of the design features of various types of engines that are installed in modern cars allows us to formulate a general idea about the peculiarities of the operation of cars with the considered types of engines. Practical meaning. The obtained results of the analysis and the given advantages and disadvantages in the use of different types of engines allow us to formulate the main directions in the development of structures and the prospects of their application in different types of cars.
Аналіз конструкцій та застосування різних типів двигунів у автомобілі
Keywords: internal combustion engine; gasoline engine; diesel engine; electric car; electric motor; hybrid car; двигун внутрішнього згоряння; бензиновий двигун; дизель; електромобіль; електродвигун; гібридний автомобіль; 629.02; 10.30977/AT.2219-8342.2023.52.0.10